Development of Student Worksheets Based on Project Based Learning Model to Improve Concept Understanding in The Biology Learning: Respiratory System Material - Tri Agustina; Syarifah Widya Ulfa (Universitas Labuhanbatu, 2024)
The demands of the 21st century extend beyond the mere mastery of knowledge; they require individuals to develop a robust set of skills, particularly in understanding complex concepts. This research focuses on creating Student Worksheets rooted in the Project Based Learning model to enhance students' comprehension in biology. To achieve this, the research employs the 4D development model, which includes four phases: Define, Design, Development, and Disseminate. Data collection involved validating the product's feasibility, gathering feedback from both teachers and students, and conducting pretests and posttests, followed by N-Gain analysis. The data analysis encompassed three main techniques: validity analysis, practical analysis, and effectiveness analysis. The findings indicated a high degree of validity, with material validation reaching 93% (categorized as